2005
DOI: 10.1167/iovs.04-0928
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA Class I and Class II Polymorphisms with Age-Related Macular Degeneration

Abstract: Significant positive and negative associations exist between HLA alleles and AMD. HLA polymorphisms influence the development of AMD, possibly via modulating choroidal immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 51 publications
1
56
1
1
Order By: Relevance
“…13 For these reasons, HLA polymorphisms have been hypothesized to modulate susceptibility to AMD. 14,15 Drusen formation and AMD progression could result from an inflammatory response to RPE injury that involves HLA and the complement systems. 11,31,32 Our finding is the first to implicate the association of an HLA class II polymorphism with AMD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 For these reasons, HLA polymorphisms have been hypothesized to modulate susceptibility to AMD. 14,15 Drusen formation and AMD progression could result from an inflammatory response to RPE injury that involves HLA and the complement systems. 11,31,32 Our finding is the first to implicate the association of an HLA class II polymorphism with AMD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Drusen, a pathologic hallmark of AMD, contain HLA class II antigens, 12 and increased HLA class II immunoreactivity has been associated with drusen formation, 13 suggesting that HLA may influence the development of AMD. Although a few small candidate gene studies found that certain HLA class I and class II polymorphisms were associated with a predisposition to AMD, 14,15 the largest genome-wide association study (GWAS) meta-analysis conducted by the AMD Gene Consortium, which included more than 77 000 subjects, did not identify any HLA polymorphisms that were independently associated with the risk of AMD. 16 The AMD Consortium meta-analysis, although well powered to detect common variants of small effect, included a number of studies that utilized genotyping arrays, with array density ranging from 165 770 to 668 238 genotyped SNPs after QC, with incomplete coverage of genetic variants in the HLA region.…”
Section: Introductionmentioning
confidence: 99%
“…and B.G., unpublished data). Finally, the single published study on MHC in AMD demonstrates modest protection for the class I locus B*4001 (P = 0.027) and the class II locus DRB1*1301 (P = 0.009) 25 . Because the protective alleles identified in this study are associated with AMD at a substantially higher statistical significance, it is very unlikely that the C2/BF association is due to LD with these and/or other loci in the MHC.…”
mentioning
confidence: 89%
“…These works present differences with ours. Thus, Goverdham studies the existing relation between ARMD and the HLA, including 100 patients with ARMD and 92 controls (12). In that work they established 4 groups of patients according to age-related eye disease study (AREDS study) of which only a part of the fourth group (N = 62) includes patients with choroidal neovascularization (less than us and not describe what kind of wet ARMD-treatable, non treatable) (23).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the immune system is involved in the development of ARMD (8)(9)(10). On the other hand, it is also known that certain genetic basis exists in this pathology (11,12).…”
Section: Introductionmentioning
confidence: 99%